Analisis Minat Muzakki Dalam Membayar Zakat Ditinjau Dari Kualitas Pelayanan dan Citra Lembaga - Nuris Tishwanah; Fitri Nur Latifah (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this study is to determine and test the effect of service quality and institutional image on muzakki's interest in paying zakat. The quality of service and the image of the institution are important factors for zakat management institutions to continue to improve. If zakat management institutions have good service quality and image in the community, it will also indirectly encourage public interest in issuing zakat and can increase the receipt of zakat funds in zakat management institutions. This study used quantitative methods by providing questionnaires to 99 respondents who paid zakat through BAZNAS. The results of the study were processed using SPSS software version 22 which showed that the quality of service had a positive but not significant influence on muzakki's interest in paying zakat. Meanwhile, the image of the institution has a positive and significant influence on muzakki's interest in paying zakat.